From Cooking Pots to Content Spots: An AIDA Analysis of @henipurnamasarii Storytelling - Amala Nadhifa; Alma Fadhilahwati; Fardh Aulia Hakim; Ihsan Ikhlasul Amal; Muhammad Fauzan Azis; Wildi Adila (Prodi Ilmu Komunikasi UTM, 2025)
This research aims to analyze the application of AIDA theory, first introduced by Strong (1925) consists of Attention, Interest, Desire, Action in @henipurnamasari's YouTube short videos. By analyzing multimodal (visual, text, and narration). This study used a descriptive qualitative approach using Spradley's qualitative data analysis (2016). The data taken from 3 types of videos, namely describing the customer, money brought, and third-party order. The research reveals how each AIDA stage is effectively crafted within a brief format. This Attention hook is established immediately through provocative titles like “Rp 400,000 meatball order for Bu Lurah,” for triggering curiosity. Interest is maintained through a step-by-step cooking demonstration presented in a relatable and personal manner. Desire arises from the narrator’s candid disclosure of slim profit margins, paired with appetizing visuals that evoke empathy and longing. Lastly, Action is softly prompted encouraging likes, subscribes, and shares. These findings demonstrate that the century-old AIDA model remains a powerful tool for structuring persuasive narratives in modern short-format digital media.